2004
DOI: 10.1159/000075290
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Chromosomal Imbalance Aberrations in Gastrointestinal Stromal Tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. Current criteria for the diagnosis of malignant GISTs do not always reliably predict patient outcomes. In order to search for genetic markers with prognostic potential, chromosomal imbalance aberrations (CIAs) were analyzed in 28 subjects with GIST using comparative genomic hybridization and correlated with clinicopathological features. Except for a small rectal tumor, CIAs were identified in all GISTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 18 publications
(39 reference statements)
1
8
0
10
Order By: Relevance
“…In cancer patients the instability is increased probably due to tumor progression. In first-degree relatives of GIT cancer patients, aberrations observed are similar to the aberrations reported in lymphocytes of GIT cancer patients in previous studies (Barletta et al 1993;Dave et al 1995;Sokova et al 1997;Pack et al1999;Guleria and Sambyal 2003;Chen et al 2004;Guleria et al 2005;Jude et al2005). A high frequency of aberrations involving specific chromosomes harboring particular genes involved, directly or indirectly, in tumorigenesis, indicates a constitutional chromosomal instability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In cancer patients the instability is increased probably due to tumor progression. In first-degree relatives of GIT cancer patients, aberrations observed are similar to the aberrations reported in lymphocytes of GIT cancer patients in previous studies (Barletta et al 1993;Dave et al 1995;Sokova et al 1997;Pack et al1999;Guleria and Sambyal 2003;Chen et al 2004;Guleria et al 2005;Jude et al2005). A high frequency of aberrations involving specific chromosomes harboring particular genes involved, directly or indirectly, in tumorigenesis, indicates a constitutional chromosomal instability.…”
Section: Discussionsupporting
confidence: 86%
“…Spontaneous chromosomal aberration in invitro cultured peripheral blood lymphocytes of pediatric cancer patients and their healthy firstdegree relatives has earlier been reported which suggests an increase in chromosomal aberration in asymptomatic relatives and points towards its consideration for biomarker studies (Bakshi et al 1999). Recurrent losses, including 1p, 14q, 10q, 13q, 15q, 18q and 22q, and gain of 5p, 12q, 17q and 20q have been reported as genetic markers with prognostic potential in gastrointestinal stromal tumors (Chen et al 2004). Though a database is required to characterize aberrations as a marker of cancer risk (Rossener et al 2005), there is evidence that increased frequency of chromosomal aberrations in blood lymphocytes is predictor of cancer (El-Zein et al2005;Boffetta et al 2007, El-Zein, 2007Ghosh et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…As a part of such mechanisms, the loss of chromosome 14q and 22q has been reported in primary GIST. ( 23,26,51,52 ) These chromosomal alterations seen in the early stage of GIST could be involved in the development of clinical GIST.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of GIST patients differs according to the tumor site; I‐GIST show more aggressive behavior than S‐GIST . Genome‐wide global studies have revealed differences in KIT or PDGFRA mutations, gene expressions and chromosomal aberrations between I‐GIST and S‐GIST . These observations suggest that further exploration of these molecular aberrations associated with the tumor site would yield clues to understanding the molecular background of the malignancy in GIST, thus widening the clinical options available to GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that differences in expression or mutation of KIT and PDGFRA are associated with the tumor site . In addition, chromosomal aberrations and gene expressions that are specific to I‐GIST have been identified in genome‐wide global studies, and these have also been shown to be adverse prognostic factors . However, these reports lack validation studies for the confirmation of the prognostic value and clinical utility.…”
mentioning
confidence: 99%